Rapid Reentry Resources: Needs Assessment of a Mobile Reentry Service Trailer for People Leaving a Superjail - Abukar, Hodman (The prison journal, 2025)
Reentry is a challenging period associated with increased risk of mortality, drug overdose, and homelessness. Mobile reentry services offer rapid support at convenient locations for individuals released from custody. We conducted a needs-assessment of a Mobile Reintegration Service located outside a detention center in Ontario, Canada, through a focus group with staff members. Applying the Strengths, Weaknesses, Opportunities, and Threats methodology, the findings revealed strengths such as the mobile service's proximity to detention center, its peer support worker program, and provision of basic needs items. Mobile reentry services offer innovative ways to support the complex needs of individuals leaving correctional institutions.